Making Vocational Training Effective for Employability - Sah, Nickesh Kumar (Journal of Technical and Vocational Education and Training, 2026)
Vocational training is important for empowering youths to link them to formal labor markets. This review paper highlights the role of vocational skill development program in addressing unemployment especially among marginalized groups and youth in Nepal. The study follows a qualitative approach with thematic analysis to explore the relationship between short-term vocational training and its outcomes. After reviewing various national and international studies, the paper focuses on key challenges, such as gender disparities in employment outcomes and other common barriers. Once there is underemployment and skill mismatch, which is evident from market saturation and economic conditions, the ultimate goal of vocational training is not achieved. These happen because the job market changes and sometimes gets too full. The paper therefore argues fair and inclusive training are imperative, while support after training is equally important. Only fair and balanced approach helps in creating equal chances and supporting long-term growth in the countries like Nepal.